Design and Implementation of Battery Control Unit Based Pulse Width Modulation for Lighting System by Solar Cell Module - Ekki Kurniawan; Alvius El Viegas; Sigit Yuwono; Septiadi, Yadi (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The utilization of renewable energy has become one of the solutions to addressing the global energy crisis. Along with the continuous rise in energy costs, conventional energy sources are becoming increasingly depleted. One example of renewable energy utilization is the use of solar energy. The energy harnessed from sunlight can be converted into electrical power through photovoltaic technology, which employs solar cells as implemented in solar power plants. However, solar power plants face several challenges, particularly in current and voltage control, which lead to inefficiencies in solar energy utilization. The system is designed to regulate current and voltage during the battery charging and discharging processes using PWM control. The experimental results show a battery charging voltage of 14 VDC and a charging current of 1.2 A, where the charging current corresponds to 10% of the battery capacity. The implemented Battery Control Unit (BCU) achieved an overall efficiency of 92%.